Reduction of Spectral Radiance Reflectance During the Annular Solar Eclipse of 21 June 2020 Observed by EPIC - Wen, Guoyong; Marshak, Alexander; Herman, Jay; Wu, Dong (Frontiers in Remote Sensing, 2022)
The annular solar eclipse on 21 June 2020 passed over desert areas (parts of Central and Eastern Africa, the southern Arabian Peninsula), partly cloudy regions (parts of South Asia and the Himalayas), and the mostly cloudy region in East Asia. Moving around the Earth-Sun Lagrange point 1 (L1), the Earth Polychromatic Imaging Camera (EPIC) instrument on the Deep Space Climate Observatory (DSCOVR) spacecraft captured three sets of images of the sunlit Earth during the eclipse, allowing us to study the impact of the solar eclipse on reflected solar radiation when the underlying surface and/or cloudy conditions in the Moon’s shadow are quite different. We analyzed EPIC images acquired during the 21 June 2020 and 21 August 2017 eclipses. We found that (1) EPIC-observed average spectral as well as spectrally averaged reflectance reductions of the entire sunlit Earth during the 21 June 2020 solar eclipse are distinctly different from those during the total solar eclipse of 21 August 2017; (2) the reduction of spectral reflectance depends strongly on underlying reflector properties, including the brightness, the area coverage of each reflector in the penumbra and the average distance to the center of the Moon’s shadow.